Competitive factors for the development of Peruvian coffee growing - Nahuamel Jacinto, Edwin (2019)
The present investigation makes an identification and evaluation of the competitive factors of the Peruvian coffee industry. For whichinitially a study was made of the current situation in which the coffee production chain is located, identifying the natural conditions that are favorable forits production, as well as the analysis of the social and economic conditions that are key to the development of the crop. As a result, the competitive factors were identified, being the following: appropriate agroecological conditions, cup quality, production technology, communication routes, quality of life, coffee institutionality, economic performance and labor market.